Delta Thigh Project : the Unmiraculous Effect of the Miracle Cream Cellulean - Thomas, Dylan P.; Carolan, Benjamin (My University, 2009)
Aminophylline, belonging to a family of molecules called methylxanthines, has been traditionally used as a drug for asthma therapy. It consists of a complex of theophylline and ethylenediamine in a ratio of approximately 2:1. Recently, studies have suggested that fatty acids are released from adipose tissue when it is exposed to aminophylline in vitro. However, no such studies have confirmed that the drug is able to penetrate skin tissue. A company, MWT inc., produces and distributes a product, "CELLULEAN" and claims that it is able to transport aminophylline across cutaneous tissue to the adipose tissue beneath; thus causing the supported finding. The aim of our study is to test this statement in a placebo-controlled experiment.
Color poster with text, diagrams, tables, and graphs describing research conducted by Dylan Thomas and Benjamin Carolan, advised by Scott Hartsell.
Keywords: Aminophylline--Physiological effect; Aminophylline--Physiological transport; Adipose tissue; Cellulean (Trademark); Posters